1997
DOI: 10.1155/1998/95861
|View full text |Cite
|
Sign up to set email alerts
|

The IL‐2/IL‐2‐Receptor Complex in the Maturation of Rat T‐Cell Progenitors

Abstract: On the basis of both the interleukin-2-receptor (IL-2R) a-chain expression on 16-day-old fetal rat thymocytes and the occurrence of interleukin-2 (IL-2) mRNA-containing cells early during rat thymus ontogeny, we have investigated the possible role of IL-2/IL-2R complex in rat T-cell maturation. For this purpose, we analyzed the effects of the addition of either recombinant rat IL-2 or anti-CD25 (OX-39)-blocking monoclonal antibodies to fetal thymus organ cultures (FTOC), established from 16-day-old rat embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The thymus provides a specialized microenvironment for T-cell development (78). Previous studies have shown that many components are involved in thymocyte development (72)(73)(74)79), including ECM integrin (80) and laminin (81,82). Laminin-2, a ligand of ␣-dystroglycan (83), and its integrin receptor VLA-6 interaction play an active role in thymocyte development by delivering cell survival and differentiation signals at specific stages of development in young adult mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thymus provides a specialized microenvironment for T-cell development (78). Previous studies have shown that many components are involved in thymocyte development (72)(73)(74)79), including ECM integrin (80) and laminin (81,82). Laminin-2, a ligand of ␣-dystroglycan (83), and its integrin receptor VLA-6 interaction play an active role in thymocyte development by delivering cell survival and differentiation signals at specific stages of development in young adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Then we examined whether ␣-dystroglycan would play a role in thymocyte development. FTOC offers a model system in which the cellular interactions involved in fetal thymocyte development can be readily monitored and manipulated and have been used widely to study thymocyte development (72)(73)(74). However, blocking Ab was routinely used to explore the function of ␣-dystroglycan in certain tissues or cells (44,(47)(48)(49).…”
Section: Blocking ␣-Dystroglycan Decreased the Number Of Dp Thymocytesmentioning
confidence: 99%